(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-1-150-162 The article reveals the vectors of practical application of the principles of the modern educational paradigm, the methodological basis of which is a system-activity approach that creates a unified educational environment in development at all stages of school education. Consistency is the basis for the intensification of the educational process, the integrative development of oral and written speech in their interrelation, and especially in-depth study of subjects and project activities. The essence of deepening is not to add scientific terms, but to discover the systemic connections of a particular linguistic element with elements of other levels, combining them into a single volumetricspheroidal syncretic whole. Project activity is directly related to the in-depth study of the subject and the development of the student’s personality, because it develops creative activity, teaches to recognize and evaluate one’s thoughts and actions, compare the result of an action with the set goal, ensures maximum socialization in the process of working in a group. A young teacher should be given samples of project lesson scenarios so that he can develop creatively independently in his teaching practice. The article presents scenarios of two double lessons in the 8th grade: familiarity with phrases is aimed at studying syntactic norms, due to the goals of practical application of knowledge in conducting masterclasses for younger students. Knowledge about the composition of a simple sentence is the basis for the formation of speech types, which is necessary for the conscious planning of one’s own creative work. Key words: system-activity technologies, practice of level education, project study of the subject, socio-didactic orientation